Beyond Tomb and Relic: Anthropological and Pedagogical Approaches to Archaeogaming - Winter, Matthew (Near Eastern archaeology, 2021)
The advent of the computer chip has radically altered human life at a global scale, and with increasing access to digital platforms it was inevitable that digitization would reshape popular culture. The video game industry is one of the fastest growing sectors in technological and entertainment industries, reaching an enormous audience. It is now estimated that some 2.5 billion people play games worldwide, with 211 million American adults, 52 percent of whom are college educated (see Rassalle in this issue) (fig. 1).